Efektivitas Massage untuk Menurunkan Nyeri pada Pasien Post Operasi Sectio Caesarea (The Effectiveness of Massage in Pain Reduction of Post Caesarean Section Patients) - Yumiati Padaka Reda Mata; Monica Kartini (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2020)
AbstractPain is one of the most common problem experienced by post caesarean section (SC) patients. Pain can lead to other impacts, such as decrease the comfort levels, impair patient mobilization, and interfere mother-baby bonding process. There are several nonpharmacological interventions to deal with pain, one of which is by doing massage, where there are several variations in the implementation of post SC maternal massage. The purpose of this literature review is to evaluate the literature on the effect of massage on decreasing intensity in post section caesarean mothers. Literature search is carried out electronically through google scholar pages, Cochrane, BMJ and Pubmed databases. The keywords used are massage, pain, caesarean, post SC, or post cesarean section. There are 11 research articles that discuss massage for decreasing maternal pain. The literature search results show that massage in post section caesarean mothers has an impact on decreasing the pain scale, providing comfort, and reducing stress. Massage is a safe and effective intervention performed in post caesarean section mothers. Keywords: massage; pain; post section caesarean AbstrakNyeri merupakan salah satu masalah utama yang dialami oleh ibu post section caesarea (SC). Nyeri dapat berdampak pada berbagai hal, diantaranya menurunnya tingkat kenyamanan pasien, mengganggu mobilisasi, dan menghambat dalam proses bonding ibu dan bayi. Terdapat beberapa intervensi nonfarmakologi untuk mengurangi nyeri, salah satunya adalah dengan massage. literature review ini bertujuan untuk mengevaluasi hasil-hasil penelitian tentang pengaruh massage dalam menurunkan intensitas nyeri pada ibu post SC. Penelusuran literatur dilakukan secara elektronik melalui google scholar, Cochrane, BMJ dan Pubmed. Kata kunci yang digunakan adalah massage, nyeri, post SC, dan post section caesarean. Terdapat 11 artikel penelitian mengenai massage untuk menurunkan nyeri maternal. Hasil penelusuran literatur menunjukkan bahwa massage pada ibu post SC bermanfaat dalam menurunkan skala nyeri, memberikan kenyamanan, dan mengurangi stress. Massage merupakan intervensi yang aman dan efektif dilaksanakan untuk ibu post SC. Kata kunci: massage; nyeri; post section caesarea